Logitech International S.A. / Siti Nuruljannah Muhamad - Muhamad, Siti Nuruljannah (2022)
According to Logitech (2021), Logitech was founded in Lausanna, Switzerland in 1981 and expanded rapidly in Silicon Valley. Logitech develops products and experiences which have a place in everyday people's lives as a Swiss company focusing on innovation and quality. Faithful to its revolutionary computer peripherals and many new market products, including the infrared cordless mouse, the thumb-operated trackball, the laser mouse and more. Logitech is a multiple branded company that designs products, which bring people together through music, gaming, video and computing, and sells products in almost all countries. Logitech also markets their products under various brands include Logitech, Logitech G, ASTRO Gaming, Ultimate Ears, Jaybird, Blue Microphone, and Streamlabs (Logitech, 2021). Based on Scartozzi et al. (2020), the Logitech G Pro Wireless is an amazing wireless gaming mouse that is powerful enough for office use. It has really good performance and is flexible inside the companion app. Its scale and form are beautiful and relaxing and are ideal for nearly all hands and grips, except little fingertip hands. It has both an ambidextrous latency design and a wired or wirelessly very low click latency. However, it induces some drag using its cord. It also has only two extra buttons on each hand, which might not be sufficient for competitive MMO players.